Análise comparativa dos impactos ambientais associados às rotas primária e secundária da produção de aço em uma usina siderúrgica : estudo de caso baseado na avaliação do ciclo de vida da estrutura metálica de um pavilhão industrial executada a partir de sucata ferrosa reciclada - Baum, Vitor Behar (2021)
The purpose of this work was to make a comparative analysis of the environmental impacts associated with the two routes of steel production in a steel mill: primary, from the smelting of iron ore in a blast furnace and the secondary, from the smelting of ferrous scrap in electric arc furnace. To fulfill this purpose, the Life Cycle Assessment (LCA) technique was used, in an approach from the cradle to the gate with options, from the incomplete life cycle, comprising the Product Stage, End of Life Scenario and Module D , the kg of steel of the metallic structure having been adopted as a declared unit, all according to the European standard EN 15804 that deals with LCA of civil construction products, and a steel recycling rate of 90%, with 10% of unusable waste sent to landfill. The LCA was carried out from a case study of the metallic structure of an industrial pavilion built with recycled ferrous scrap, located in the city of Sapucaia do Sul/RS. As main results, the net environmental benefits from the adoption of the secondary production route and the high recycling potential of ferrous scrap, in terms of total emissions of CO2 eq and total primary energy demanded were -1.81x10^5 kg CO2 eq and -1,76x10^6 MJ, respectively, and the negative sign, in these values, means the volume of CO2 eq emissions that was avoided from being released into the atmosphere and the total demanded primary energy that was saved, when compared with the primary production route of the steel in a steel mill. Based on these results, it can be concluded that the secondary route is beneficial to the natural environment, in comparison with the primary route, since it mitigates CO2 eq emissions and saves total primary energy demanded in the production of steel in a steel plant.